A note on the measurement of the U238 cadmium ratio - Arcipiani, Biagio; Ricabarra, Delfina; Ricabarra, Guillermo (Taylos & Francis, 1962)
Fil: Arcipiani, Biagio European Atomic Energy Community; Italia